Paper-Based Electrochemical Devices for the Pharmaceutical Field: State of the Art and Perspectives - Antonacci, Amina; Scognamiglio, Viviana; Mazzaracchio, Vincenzo; Caratelli, Veronica; Fiore, Luca; Moscone, Danila; Arduini, Fabiana (Frontiers in Bioengineering and Biotechnology, 2020)
The current international pharmaceutical scenario encompasses several steps for drug production with complex and extremely long procedures. In the last few decades, scientific research has been trying to offer valid and reliable solutions to replace or support conventional techniques, in order to facilitate drug development procedures. These innovative approaches may have extremely positive effects in the production chain supplying fast and cost-effective quality and safety tests on active pharmaceutical ingredients and their excipients. In this context, the exploitation of electrochemical paper-based analytical devices (ePADs) is still in its infancy, but particularly promising for its fascinating properties in the detection of active pharmaceutical ingredients and excipients in tablets, capsules, suppositories, and injections, as well as for pharmacokinetic bioanalysis in real samples.